Psychometric Properties of the Service Leadership Attitude Scale in Hong Kong - Shek, Daniel T. L.; Chai, Wen Yu (Frontiers in Psychology, 2019)
Positive attitude to service leadership is fundamental for the development of successful leadership qualities in the service-dominated economy. The purpose of this study was to examine the psychometric properties of the 46-item Service Leadership Attitude Scale (SLA) in Hong Kong. A total of 2,240 undergraduate students in Hong Kong (mean age = 20.44+1.64 years; 66.9% were female) completed a questionnaire containing the 46-item SLA and other leadership-related scales. The psychometric properties of SLA were assessed using confirmatory factor analyses (CFA), reliability analyses, measurement invariance tests, and convergent validity test. Previous exploratory factor analyses suggested a seven-factor model of SLA which was supported by CFA in this study. By adding an additional dimension (“Implicit leadership theory”) in the scale, the final eight-factor model with 46 items showed superior fit using CFA. Factorial invariance tests showed that the factor structure was invariant in terms of construct dimensionality, factor loadings, intercepts, and factor covariance across gender and subgroups split based on “odd” and “even” case numbers. Convergent validity tests showed that the scale scores were correlated with several leadership-related scales. The scale and subscales also demonstrated good internal consistency reliability. This study is the first scientific work to validate a measure of attitude to service leadership via confirmatory factor analyses. It contributes significantly to the development and validation of measures of attitude to service leadership, particularly in the higher education sector.